Electron densities inferred from plasma wave spectra obtained by the Waves instrument on Van Allen Probes. Issue 2 (10th February 2015) - Kurth, W. S.; De Pascuale, S.; Faden, J. B.; Kletzing, C. A.; Hospodarsky, G. B.; Thaller, S.; Wygant, J. R.
Abstract The twin Van Allen Probe spacecraft, launched in August 2012, carry identical scientific payloads. The Electric and Magnetic Field Instrument Suite and Integrated Science suite includes a plasma wave instrument (Waves) that measures three magnetic and three electric components of plasma waves in the frequency range of 10 Hz to 12 kHz using triaxial search coils and the Electric Fields and Waves triaxial electric field sensors. The Waves instrument also measures a single electric field component of waves in the frequency range of 10 to 500 kHz. A primary objective of the higher‐frequency measurements is the determination of the electron density ne at the spacecraft, primarily inferred from the upper hybrid resonance frequency fuh. Considerable work has gone into developing a process and tools for identifying and digitizing the upper hybrid resonance frequency in order to infer the electron density as an essential parameter for interpreting not only the plasma wave data from the mission but also as input to various magnetospheric models. Good progress has been made in developing algorithms to identify fuh and create a data set of electron densities. However, it is often difficult to interpret the plasma wave spectra during active times to identify fuh and accurately determine ne. In some cases, there is no clear signature of the upper hybrid band, and the low‐frequency cutoff of the continuum radiation is used. We describe the expected accuracy of ne and issues in the interpretation of the electrostatic wave spectrum.